Using squat repetition maximum testing to determine hamstring resistance training exercise loads - Ebben, W. P.; Long, N. J.; Pawlowski, Z. D.; Chmielewski, L. M; Clewien, R. W; Jensen, R. L. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine whether there is a linear relationship between the squat and a variety of hamstring resistance training exercises, and whether this relationship differs on the basis of sex. This study also sought to create prediction equations for the determination of hamstring exercise load based on the squat load. Repetition maximums of the squat, as well as 4 common hamstring resistance training exercises including the seated leg curl, stiff leg dead lift, single leg dead lift, and good morning exercise, were determined for each subject. Subjects included 21 men and 13 women collegiate athletes. Data were evaluated using linear regression analysis to predict hamstring exercise loads from 6 repetition maximum squat data. Results of the analysis of all subjects indicated that squat load was a significant predictor of loads for each of the hamstring exercises. However, separate analysis of women revealed that squat load was not a significant predictor of loads for any of the hamstring exercises. Analysis of the men revealed that squat was a significant predictor of load for the seated leg curl (R2 = 0.58, p < 0.001), stiff leg dead lift (R2 = 0.82, p < 0.001), single leg stiff leg dead lift (R2 = 0.80, p < 0.001), and good morning (R2 = 0.79, p < 0.001) exercises. On the basis of the analysis of the men, the following prediction equations were devised for each exercise: (1) seated leg curl load = squat load (0.186) + 10.935 kg, (2) stiff leg deadlift load = squat load (1.133) - 86.331 kg, (3) single leg stiff leg deadlift load = squat load (0.443) - 3.425 kg, and (4) good morning load = squat load (0.961) - 105.505 kg. Thus, results from testing core exercises such as the squat can provide useful data for the assignment of loads for assistance exercises.